2020
DOI: 10.1038/s41467-020-19922-3
|View full text |Cite|
|
Sign up to set email alerts
|

Reproductive phasiRNAs regulate reprogramming of gene expression and meiotic progression in rice

Abstract: Plant spermatogenesis is a complex process that directly affects crop breeding. A rapid change in gene abundance occurs at early meiosis prophase, when gene regulation is selective. However, how these genes are regulated remains unknown. Here, we show that rice reproductive phasiRNAs are essential for the elimination of a specific set of RNAs during meiotic prophase I. These phasiRNAs cleave target mRNAs in a regulatory manner such that one phasiRNA can target more than one gene, and/or a single gene can be ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 56 publications
1
62
0
Order By: Relevance
“…DAZAP1 is potentially associated with stress granules in puromycin-treated iPS cells [42]. Furthermore, when the Recent works showed that the gene expression profile changes dramatically at the early meiotic prophase I in maize PMCs [49], and the rice reproductive phased siRNAs (phasiRNAs) associated with MEL1 Argonaute regulate the reprogramming of gene expression through the direct RNA cleavage [50,51]. In addition to phasiRNAs-MEL1 mediated mRNA degradation, some MEL2 granules may be involved in the decay process working alongside P-bodies to remove a subset of transcripts that are dispensable for progression through meiosis.…”
Section: Discussionmentioning
confidence: 99%
“…DAZAP1 is potentially associated with stress granules in puromycin-treated iPS cells [42]. Furthermore, when the Recent works showed that the gene expression profile changes dramatically at the early meiotic prophase I in maize PMCs [49], and the rice reproductive phased siRNAs (phasiRNAs) associated with MEL1 Argonaute regulate the reprogramming of gene expression through the direct RNA cleavage [50,51]. In addition to phasiRNAs-MEL1 mediated mRNA degradation, some MEL2 granules may be involved in the decay process working alongside P-bodies to remove a subset of transcripts that are dispensable for progression through meiosis.…”
Section: Discussionmentioning
confidence: 99%
“…One study in pummelo predicted and verified targets in trans with gene ontologies of broad terms but also including PCD and pollen development (Fang et al 2020). By now, two pioneering study in rice meiocytes finally found indeed RNA degradation of target genes of reproductive 21nt-phasiRNAs (Jiang et al 2020;Zhang et al 2020c). In rice meiocytes, target genes were enriched for carbohydrate biosynthesis and metabolism, and also included OsDMC1B, a meiotic gene (Jiang et al 2020).…”
Section: Tasirnasmentioning
confidence: 97%
“…Another study gained insight on genes targeted for degradation in rice anthers through degradome data from whole rice spikelets of WT and of mutants in MEL1, the rice AGO5 which binds phasiRNA. Intriguingly, many RLKs were identified as phasiRNA target genes, among them MSP1 (Zhang et al 2020c). This re-defines part of the reproductive phasiRNAs as tasiRNAs, with specific target genes with roles and/or high abundance in meiosis and anther development (Dukowic-Schulze et al 2014;Wang et al 2016).…”
Section: Tasirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability or generation of a stable male sterile line is the prerequisite to produce high-quality hybrids. Over the years, EGMS lines have been broadly used for two-line systems of hybrid breeding because of (1) availability of germplasm resources and (2) reversibility of fertility via the manipulation of environmental factors ( Chen and Liu, 2014 ; Xue et al, 2018 ; Zhu et al, 2020 ; Zhang Y. et al, 2020 ). On the other hand, abrupt environmental fluctuations have always posed a serious threat for their wider applications.…”
Section: Biotechnological Strategies To Develop Male Sterility and Hymentioning
confidence: 99%